ҚАРАҚАЛПАҚ ӘДЕБИЯТТАНЫЎ ИЛИМИНДЕ ЛИРИКАЛЫҚ ҚАҲАРМАН ОБРАЗЫНЫҢ ИЗЕРТЛЕНИЎИ - Дабылов, П.А. (FAN va JAMIYAT, 2016)
The article is devoted to the study of lyrical image in Karakalpak literature. There have been analysed the theoretical views of the scholars S.Akhmedov, K.Kamalov, T.Mambetniyazov, K.Xudaybergenov and K.Orazimbetov. The author studies the peculiarities of lyricism, the author‘s image and lyrical heroes. The spiritual world of the hero plays a great role in the creation of lyrical character